ผลของวิธีสอนมาตรฐาน ประเภทมโนทัศน์ เพศ และผลสัมฤทธิ์ต่อการเรียนมโนทัศน์ - อรอนงค์ สาราภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1978)
The purpose of this research was to study the effects of teaching paradigm, concept type, sex and achievement on concept learning. Subjects were 160 students in Mathayom Suksa IV and Mathayom Suksa V of Saravitaya School, academic year 1977. The subjects were divided in two groups each consisted of 40 males and 40 females. In each groups, half of the males and half of the females had high academic achievement and the other halves had low academic achievement. The two groups of subjects received different modes of concept teaching; namely a selection paradigm group and a reception paradigm group. The experiment had employed yoking procedure. Each subject learned 4 concepts; affirmation, conjunction, relational and disjunction individually. The stimulus material was constructed according to Bruner and others to study the concept learning. Multifactor Analysis of Variance - Repeated measures on one factor was used to analyze the data. Teaching paradigm, concept type, sex and achievement were independent variables whereas the number of trials to criterion was dependent variable. Newman – Keuls multiple comparisons were performed on the number of trials to criterion for learning different concept types. The results were: 1. The selection paradigm was more efficient than the reception paradigm for concept learning. (P< .01) 2. There was significant difference (P <.01) for learning different concept types. The increasing order of difficulty were affirmation, conjunction, relational and disjunction. 3. The paradigm by the different concept types interaction was significant. (P <.01) The selection paradigm was more efficient for learning affirmation, conjunction and relational whereas the reception paradigm was more efficient for learning disjunction. 4. High achievement students learned concepts more efficiently than low achievement students. (P <.01) 5. There was no significant difference (P <.O5) for concept learning between male and female students.